(untitled) (Educational Dimension, 2021)
In the 21st century, the rapid pace and complexity of economic, technological and cultural change require adults to adapt to globalization throughout life. These challenges of today not only emphasize the importance of lifelong learning in general, but require adults to continue to receive more information, improve previously acquired knowledge and skills, to adapt to the new rhythm of life. The present article analyzes the state and outlines the features of adult education in the postwar period, in the period after the collapse of the USSR and in the years of Independence of Ukraine. The author identifies and discloses factors that hinder the qualitative development of the adult education system in Ukraine, such as: imperfection of legal support for adult education, the demographic situation in the country, high unemployment and poverty, fragmentary research on adult education and uncertainty about practice training of andragogy specialists. Possible ways to improve the system of adult education in Ukraine are suggested.